Design and Implementation of ARM-Based Children's Accompanying Robot - Yonggang Zhang, Zhengjin Li, Hong He, Ying Hu (Forest Chemicals Review, 2022)
With the development of social economy and the improvement of people's living standards, people's work rhythm is getting faster and faster, and people have more and more work matters to deal with. Many parents need to work outside during the daytime, leaving only minors alone at home. The minor faces the dilemma of "nothing to say" in the family. This kind of growth environment is extremely detrimental to the physical and mental health of minors, so the care and companionship of minors is becoming increasingly important. In view of the situation that minors often stay alone at home, the author of this paper designed an ARM-based minor companion robot to cope with such situations. This system is divided into three parts: ARM robot part, Linux server part, cloud data processing part. This product will be used in family to realize voice chat with minors. The ARM demo board is used as the human-machine interaction carrier. The ARM front end, Linux server and the cloud cooperate with each other to complete the user-specified needs. The ARM robot part includes: user interaction interface design, collection and playback of ALSA voice data, and transmission of voice data and Linux server. The Linux server part includes: real-time monitoring whether the system memory receives audio data uploaded by the ARM robot; use the received audio data to generate text data by adopting iFLY voice recognition, and then uploading the text data to Alibaba Cloud to obtain a response result, converging of cloud computing, big data and artificial intelligence, and finally synthesizing the response content into an audio file by combining with iFLY Cloud voice and passing it to the ARM robot. After receiving the data, the cloud performs data analysis and calculation to obtain the optimal solution and returns it to the server. Through this division of labor and cooperation, the robot can normally "talk" to human. The thesis designed the overall scheme of the design and implementation of ARM-based minor companion robot, and then elaborately introduced the resources used by the system, including the establishment of QT interface, the processing of audio data by ALSA, and the monitoring and processing of data by Linux server, the establishment of NFS service, Linux server and cloud data exchange. Finally, this thesis proved through experiments that the system achieves the purpose of intelligent and efficient connection between machine and human.